Devaluation, the trade balance, and the balance of payments - Miles, Marc A. (New York : M. Dekker, 1978)
This book uses empirical methods to test a long-held tenet of international economic theory and policy making: the belief that devaluation improves the trade balance.
Includes bibliographical references : p. 139-142 and index..
osc 21/02/17
Loans
Keywords: Foreign exchange rates; Devaluation of currency; Balance of trade; Balance of payments